Automated Payment and Contract Management in the Construction Industry by Integrating Building Information Modeling and Blockchain-Based Smart Contracts - Katharina Sigalov; Xuling Ye; Markus König; Philipp Hagedorn; Florian Blum; Benedikt Severin; Michael Hettmer; Philipp Hückinghaus; Jens Wölkerling; Dominik Groß (Applied Sciences, 2021)
Construction projects usually involve signing various contracts with specific billing procedures. In practice, dealing with complex contract structures causes significant problems, especially with regard to timely payment and guaranteed cash flow. Furthermore, a lack of transparency leads to a loss of trust. As a result, late or non-payment is a common problem in the construction industry. This paper presents the concept of implementing smart contracts for automated, transparent, and traceable payment processing for construction projects. Automated billing is achieved by combining Building Information Modeling (BIM) approaches with blockchain-based smart contracts. Thereby, parts of traditional construction contracts are transferred to a smart contract. The smart contract is set up using digital BIM-based tender documents and contains all of the relevant data for financial transactions. Once the contracted construction work has been accepted by the client, payments can be made automatically via authorized financial institutions. This paper describes the framework, referred to as BIMcontracts, the container-based data exchange, and the digital contract management workflow. It discusses the industry-specific requirements for blockchain and data storage and explains which technical and software architectural decisions were made. A case study is used to demonstrate the current implementation of the concept.